H3K4 Methyltransferase Activity Is Required for MLL4 Protein Stability. Issue 13 (30th June 2017) - Jang, Younghoon; Wang, Chaochen; Zhuang, Lenan; Liu, Chengyu; Ge, Kai
Abstract: Transcriptional enhancers play a key role in cell type-specific gene expression and cell fate transition. Enhancers are marked by histone H3K4 mono- and di-methylation (H3K4me1/2). The tumor suppressor MLL4 (KMT2D) is a major enhancer H3K4 mono- and di-methyltransferase with a partial functional redundancy with MLL3 (KMT2C). However, the functional role of MLL4 enzymatic activity remains elusive. To address this issue, we have generated MLL4 enzyme-dead knock-in (KI) embryonic stem (ES) cells and mice, which carry Y5477A/Y5523A/Y5563A mutations in the enzymatic SET domain of the MLL4 protein. Homozygous MLL4 enzyme-dead KI ( Mll4 KI/KI ) mice are embryonic lethal and die around E10.5, which phenocopies Mll4 knockout mice. Interestingly, enzyme-dead MLL4 protein in ES cells is highly unstable. Like Mll4 knockout ES cells, Mll4 KI/KI ES cells show reduced levels of H3K4me1/2. Furthermore, we show that ectopic expression of histone H3.3 lysine 4-to-methionine (K4M) mutant, which reduces endogenous H3K4 methylation levels in ES cells, decreases the protein stability of MLL3 and MLL4 but not that of H3K4 methyltransferases SET1A (KMT2F) and SET1B (KMT2G). Taken together, our findings indicate that MLL4 protein stability is tightly regulated by its H3K4 methyltransferase activity. Graphical Abstract: Highlights: MLL4 enzymatic activity is essential for early embryonic development. H3K4 methyltransferase activity is required for MLL4 protein stability. MLL3/MLL4 stability may be regulated by cellular H3K4 methylation levels.